Diagnosis and treatment of lung disease associated with alpha one‐antitrypsin deficiency: A position statement from the Thoracic Society of Australia and New Zealand*. Issue 3 (6th February 2020) - Dummer, Jack; Dobler, Claudia C.; Holmes, Mark; Chambers, Daniel; Yang, Ian A.; Parkin, Lianne; Smith, Sheree; Wark, Peter; Dev, Anouk; Hodge, Sandra; Dabscheck, Eli; Gooi, Julian; et al.
ABSTRACT: AATD is a common inherited disorder associated with an increased risk of developing pulmonary emphysema and liver disease. Many people with AATD‐associated pulmonary emphysema remain undiagnosed and therefore without access to care and counselling specific to the disease. AAT augmentation therapy is available and consists of i.v. infusions of exogenous AAT protein harvested from pooled blood products. Its clinical efficacy has been the subject of some debate and the use of AAT augmentation therapy was recently permitted by regulators in Australia and New Zealand, although treatment is not presently subsidized by the government in either country. The purpose of this position statement is to review the evidence for diagnosis and treatment of AATD‐related lung disease with reference to the Australian and New Zealand population. The clinical efficacy and adverse events of AAT augmentation therapy were evaluated by a systematic review, and the GRADE process was employed to move from evidence to recommendation. Other sections address the wide range of issues to be considered in the care of the individual with AATD‐related lung disease: when and how to test for AATD, changing diagnostic techniques, monitoring of progression, disease in heterozygous AATD and pharmacological and non‐pharmacological therapy including surgical options for severe disease. Consideration is also given to broader issues in AATD that respiratory healthcare staff may encounter: genetic counselling, patient support groups, monitoring for liver disease and the need to establish national registries for people with AATD in Australia and New Zealand.